Topical effects of haruan (Channa striatus bloch)-based cream on inflammation in rats and mice - Abedi, Sadegh (2012)
Natural treatments with little side effects can be very good substitutes as chemical therapeutics. Haruan (Channa striatus, Channidae) is a stripped snakehead, tropical, freshwater, carnivorous, and air breathing fish species, indigenous to Malaysia. The main objective of the current study was to study the topical anti-inflammatory properties of haruan (Channa striatus) based cream in acute and chronic inflammation induced animals. Changes in ear weight, thickness, and myeloperoxidase level in croton oil-induced mice ear edema were measured as acute anti-inflammatory activities, and changes in right hind paw volume in complete Freund’s adjuvant-induced arthritis was measured as chronic anti-inflammatory activity of haruan based cream. Hydrocortisone 1 % cream and diclofenac 1% cream were applied as reference drug in acute and chronic phases; respectively. At 24 hours, the treatment dosages of haruan based cream reduced ear edema by 68 %,78 %, and 98 %, respectively, whereas hydrocortisone is 92 %. Data also showed that haruan based cream of 10 %, at 24 hours was significantly (p < 0.05) more effective than 5% in inhibiting ear edema. Mean mass of ear punch biopsies in treatment groups 1, 2, and 3, and hydrocortisone were 1.63 ± 0.08, 1.57 ± 0.06, 1.32 ± 0.01, and 1.50 ± 0.05 mg (mean ± SEM), respectively, compared to 2.19 ± 0.17 mg (mean ± SEM) in vehicle group. Mean MPO concentration of biopsies taken from ears treated with hydrocortisone cream 1% and haruan based cream at 1%, 5%,and 10% were 3.20 ± 0.080, 3.74 ± 0.110, 3.44 ± 0.060, and 2.72 ± 0.025 ng/ml (mean ± SEM), respectively. Average of paw volume changes at 21 days after inducing arthritis, in animals treated with diclofenac sodium cream 1%, and haruan based cream 1%, 5%, and 10% were 0.390 ± 0.122, 0.465 ± 0.080, 0.535 ± 0.190,and 0.043 ± 0.016 ml (mean ± SEM), respectively. In comparison with vehicle group (2.76 ml), all three treatment groups and reference group had significantly reduced paw edema (p < 0.05). As conclusion, it is suggested that the topical antiinflammatory effects of haruan based cream is contributed by its bioactive substances content especially fatty acids and amino acids.